Architecting Real-Time Analytics: A Comprehensive Guide to Cloud Data Engineering - Selvakumar Alagarsamy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the architectural foundations and implementation strategies for real-time analytics in cloud data engineering environments. The article examines the evolution of data processing systems, focusing on how modern architectures handle streaming data, complex event processing, and distributed computing challenges. The article demonstrates the transformative impact of real-time analytics on business operations through a detailed analysis of core architectural components, including data ingestion layers, processing frameworks, and storage solutions. The article encompasses advanced visualization techniques, pipeline management strategies, and security considerations, providing insights into building robust and scalable real-time analytics systems. The article also evaluates implementation best practices, examining performance optimization techniques, security frameworks, and compliance requirements. By analyzing emerging trends and integration challenges, the research offers valuable insights for organizations seeking to implement or enhance their real-time analytics capabilities, while emphasizing the importance of balancing performance, security, and operational efficiency in modern data architectures.